miR-484: A Possible Indicator of Drug-Induced Pulmonary Fibrosis - Takashi Konaka; Masashi Kawami; Ayano Yamamoto; Ryoko Yumoto; Mikihisa Takano (Frontiers Media S.A., 2020)
Background: Drug-induced lung injury leads to serious lung diseases, such as pulmonary fibrosis. We demonstrated in an alveolar epithelial cell line A549/ABCA3 that certain microRNAs were associated with bleomycin induced epithelial-mesenchymal transition (EMT) which is closely related to pulmonary fibrosis. In this study, we focused on the role of miR-484 in drug-induced EMT using A549/ABCA3 cells and a mouse lung injury model. Methods: The expression of EMT-related genes and miR-484 was detected by real-time polymerase chain reaction. miR-484-targeted proteins were analyzed by Western blot. Pulmonary fibrosis mouse model was prepared by the intratracheal administration of BLM. As miR-484 is known to target SMAD2 and zinc finger E-box binding homeobox 1 (ZEB1), which are the well-known EMT-related transcription factors, we assessed the effects of a miR-484 inhibitor or mimic on the mRNA/protein expression of both the factors. Results: We found that bleomycin significantly suppressed the intracellular expression and extracellular release of miR-484 in A549/ABCA3 cells. Moreover, the miR-484 mimic and inhibitor showed no drastic effects on the expression of the EMT-related transcription factors. In addition, the miR-484 mimic had no effect on the bleomycin-induced altered mRNA expression of the α-smooth muscle actin, a representative EMT marker. This suggested that miR-484 did not directly contribute to bleomycin-induced EMT in A549/ABCA3 cells. In contrast, the significant decrease in miR-484 expression in the lung tissue or plasma of bleomycin-administered mice suggested that miR-484 expression was closely correlated with bleomycin-induced lung injury. Conclusions: These findings indicate that miR-484 could be a novel diagnostic indicator for drug-induced pulmonary fibrosis.